Activation, Immune Polarization, and Graft-versus-Leukemia Activity of Donor T-cells are Regulated by Specific Subsets of Donor Bone Marrow Antigen-Presenting Cells in Allogeneic Hematopoietic Stem Cell Transplantation() - Li, Jian-Ming (2009)
We investigated the roles of specific subsets of donor APCs purified from bone marrow in donor T cell activation and graft-vs-leukemia (GvL) activity in murine models of hemopoietic stem cell transplantation. Lineage(−)CD11c(+) APC precursors were separated from donor bone marrow based on expression of CD11b. Transplanting lineage(−)CD11c(+)CD11b(−) APC (CD11b(−) APC) in combination with c-kit(+)Sca-1(+)lineage(−) hemopoietic stem cells (HSC) and congenic donor T cells led to increased donor CD4(+) and CD8(+) T cell proliferation and higher donor T cell chimerism than with transplanting grafts containing HSC, T cells, and lineage(−)CD11c(+)CD11b(+) APCs (CD11b(+) APC), or grafts containing only HSC and T cells. Transplanting CD11b(−) APCs induced Th1/type 1 cytotoxic T lymphocyte donor T cell immune polarization and enhanced GvL activity of donor T cells without increased graft-vs-host disease in both MHC- and minor histocompatibility Ag-mismatched murine hemopoietic stem cell transplantation models, whereas CD11b(+) APCs led to Th2/type 2 cytotoxic T lymphocyte donor T cell immune polarization. Donor CD11b(−) APCs were plasmacytoid dendritic cell progenitors (>90% CD317; PDCA-1(+)) and up-regulated CD80, CD86, and IL-12 during alloantigen presentation, whereas CD11b(+) APCs expressed Gr-1 and up-regulated expression of programmed death ligands-1 and 2 after activation. These results are the first to show that manipulation of the content of donor APCs in allogeneic HSC grafts can regulate donor T cell immunity and enhance GvL without increasing graft-vs-host disease activity.